(untitled) (KULT_online, 2010)
This edited volume follows on the heels of previous projects by Jens Bergmann and Bernhard Pörksen, in each of which a central issue of media society was focused on journalistically and explored in cooperation with students. For this, the third project, they take on the subject of scandal as a journalistic call to action. At the centre of this volume are questions such as: what has the stuff of public outcry, and what doesn’t? (And in which context?) Who gains and who loses from sensational news, and what does it lead to? How are scandals started and monitored, and how can one defend oneself against them? The text examines the phenomenon of scandal in conversations from many different perspectives, and claims to get to the very core of the matter. In 29 interviews, people who are variously qualified as experts on the topic give their own controversial, surprising, and poignant answers. Among those who get their chance to speak here are kidnap victim Natascha Kampusch, bicyclist Patrick Sinkewitz, the politician Gabriele Pauli, media barrister Matthias Prinz, investigative journalist Günter Wallraff, and actress Désirée Nick.